Control Mechanisms for Ecological-Economic Systems - Burkov, Vladimir N.; Novikov, Dmitry A.; Shchepkin, Alexander V. (Studies in Systems, Decision and Control,, 2015)
This monograph presents and analyzes the optimization, game-theoretic and simulation models of control mechanisms for ecological-economic systems. It is devoted to integrated assessment mechanisms for total risks and losses, penalty mechanisms, risk payment mechanisms, financing and costs compensation mechanisms for risk level reduction, sales mechanisms for risk level quotas, audit mechanisms, mechanisms for expected losses reduction, economic motivation mechanisms, optimization mechanisms for regional environmental (risk level reduction) programs, and mechanisms for authorities' interests coordination. The book is aiming at undergraduate and postgraduate students, as well as at experts in mathematical modeling and control of ecological economic, socioeconomic and organizational systems.